Packaging agent for anti-accident SiC / SiC nuclear fuel cladding tube composite port packaging

By introducing high thermal conductivity SiC phase and one-dimensional SiC whiskers into the glass ceramic encapsulator, a co-enhanced connection layer is formed, which solves the problem of insufficient performance of the SiC/SiC fuel clad tube connection layer and improves mechanical properties and thermal conductivity , enhances structural stability and safety margin in accident conditions.

CN119263644APending Publication Date: 2025-01-07SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310830288.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing glass-ceramic connection layer of the accident-resistant SiC/SiC fuel clad tube and the SiC end plug is insufficient, resulting in low thermal conductivity and poor structural stability. Especially in the LOCA state, the thermal stress is significant, which affects the safety margin of the nuclear power plant.

Method used

Introduce one-dimensional SiC whiskers with high thermal conductivity and excellent mechanical properties into traditional glass ceramic encapsulators. By regulating the ratio of the encapsulator, a glass ceramic connecting layer is formed with SiC whiskers and SiC particles co-enhanced, improving the mechanical and thermal properties and structural stability.

Benefits of technology

It significantly improves the mechanical properties and thermal conductivity at the joints, reduces thermal stress, and enhances structural stability and safety margin in accident conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263644A_ABST
    Figure CN119263644A_ABST
Patent Text Reader

Abstract

The invention relates to a packaging agent for accident-resistant SiC / SiC nuclear fuel cladding tube composite port packaging. The encapsulating agent is prepared from glass powder, SiC powder, SiC whiskers, a binding agent and a solvent, wherein the glass powder comprises the components of MgO, Al2O3, SiO2 and ZrO2; the molar ratio of MgO to Al2O3 to SiO2 to ZrO2 in the glass powder is (15 to 40) to (10 to 25) to (35 to 50) to (5 to 10); the volume ratio of the glass powder to the SiC powder to the SiC whiskers to the binding agent to the solvent is (20-35): (5-10): (5-10): (3-50): (45-60).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to nuclear fuel cladding tube packaging technology, and in particular relates to an encapsulant used for packaging accident-resistant SiC / SiC nuclear fuel cladding tube composite ports. Background Art

[0002] Based on the advantages of ① nuclear power generation does not produce greenhouse gas CO2; ② nuclear fuel has high energy density; ③ greatly reduce and stabilize the cost of power generation; ④ abundant nuclear resources, my country has formulated a nuclear power priority development strategy, planning to reach a total installed capacity of 136 million kW by 2030, and nuclear power generation will reach 11.8% of the total electricity. Pressurized water reactor is the earliest developed and most widely used reactor type in the world. After the development process of military first and then civilian, from ship to land, as of December 2021, the total number of pressurized water reactors in large nuclear power plants in operation in the world exceeds 300, accounting for nearly 70% of the total number of nuclear power plants; the total number of pressurized water reactors in large nuclear power plants in operation in my country exceeds 50, accounting for as high as 96% of the total number of nuclear power plants. Fuel rods are the core components of the reactor core, the place where the nuclear fission chain reaction occurs, and the heat source of nuclear power. They are composed of fuel cores, fuel cladding tubes, compression springs, upper and lower end plugs, etc. The connection between the fuel cladding tubes and the upper and lower end plugs is often the structural weak point of the components. Its life and stability under normal and accident conditions are closely related to the safety margin of the reactor. At present, commercial pressurized water reactor fuel elements usually use welding technology to connect zirconium alloy fuel cladding tubes and zirconium alloy upper and lower end plugs. However, the Fukushima nuclear accident in Japan revealed a major safety defect that zirconium alloy reacts with high-temperature water vapor to produce hydrogen and melt under severe loss of coolant accidents.

[0003] In the post-Fukushima era, the development of accident-tolerant fuel elements is a hot research direction for nuclear materials in the world. SiC / SiC composite materials have excellent mechanical / thermal properties, low thermal neutron absorption cross section, and corrosion resistance, and are the most promising materials for accident-tolerant fuel cladding tubes. SiC / SiC cladding tubes are special components with thin walls and high aspect ratios. The connection / packaging technology between their upper and lower ends and SiC end plugs is a key core issue that needs to be solved urgently. Considering that ① the maximum operating temperature of domestic third-generation SiC continuous fibers is relatively low; ② in order to ensure the structural integrity of thin-walled components, a low / no pressure connection process should be adopted; ③ the mechanical and thermal matching characteristics of the connection layer with the SiC / SiC composite material and the SiC end plug, the use of glass-ceramic-based connectors for port packaging is the most feasible and simple method.

[0004] Chinese patents (publication numbers CN110903102A, CN109336634B and CN112851389A) disclose methods for connecting nuclear SiC / SiC composite materials or SiC ceramics with CaO-Y2O3-Al2O3-SiO2, CaO-MgO-Al2O3-SiO2 and CaO-Al2O3-SiO2-Li2O glass ceramics, respectively. However, oxide glass ceramics connection has the inherent defect of low thermal conductivity, which not only reduces the heat exchange efficiency between nuclear fuel and coolant, but also forms a great thermal stress between SiC / SiC cladding tube and SiC end plug when high heat flux gradient acts under LOCA state. Taking the above factors into consideration, in the existing glass ceramic connection process, adding one-dimensional SiC whiskers and SiC particles of the same quality as the connecting components is an effective method to improve the thermal properties of the connection and improve the structural stability of the connecting components under LOCA state. Summary of the invention

[0005] The present invention aims to overcome the defect of insufficient performance of the glass-ceramic connecting layer between the existing accident-resistant SiC / SiC fuel cladding tube and the SiC end plug. The present invention provides a one-dimensional SiC whisker that introduces a high thermal conductivity SiC phase and excellent mechanical properties into a traditional glass-ceramic encapsulant. By adjusting the ratio of the encapsulant, a glass-ceramic connecting layer reinforced with SiC whiskers and SiC particles is formed, thereby effectively improving the mechanical and thermal properties of the cladding tube end plug connection and the structural stability under the LOCA state.

[0006] In the first aspect, the present invention provides an encapsulant for accident-resistant SiC / SiC nuclear fuel cladding tube composite port encapsulation, comprising: glass powder whose components are MgO, Al2O3, SiO2, and ZrO2, SiC powder, SiC whiskers, a binder, and a solvent; the molar ratio of MgO, Al2O3, SiO2, and ZrO2 in the glass powder is (15-40): (10-25): (35-50): (5-10); the volume ratio of the glass powder, SiC powder, SiC whiskers, binder, and solvent is (20-35): (5-10): (5-10): (3-50): (45-60).

[0007] Preferably, the particle size distribution of the SiC powder is 20 μm: 5 μm: 0.5 μm = 5: 3: 2, and the purity is > 99%.

[0008] Preferably, the SiC whisker has an aspect ratio of (20-50):1, a diameter of 0.2-0.5 μm, and a purity of >99%.

[0009] Preferably, the binder is a compound of phenolic resin and silicone resin in a mass ratio of (1-3):1; preferably 2:1.

[0010] Preferably, the solvent is at least one of xylene, acetone and cyclohexane, and the purity is greater than 99%.

[0011] In a second aspect, the present invention further provides a method for preparing the encapsulant, comprising: (1) High-purity MgO, Al2O3, SiO2, and ZrO2 powders are mixed in a certain molar ratio, placed in a crucible, heated, and stirred until melted and clarified, and then quenched into glass powder and ground; (2) The obtained glass powder, SiC powder, SiC whisker, binder and solvent are mixed to obtain a paste-like composite port encapsulant.

[0012] Preferably, in step (1), the particle size of the high-purity MgO, Al2O3, SiO2, and ZrO2 powders is 0.5 to 10 μm, and the purity is >99%.

[0013] Preferably, in step (1), the heating temperature is 1500-1700°C for 30-120 min; the stirring rate is 30-60 rpm / min for 60-180 min; and the median diameter of the powder after grinding is 0.5-10 μm.

[0014] In a third aspect, the present invention provides a method for encapsulating the composite port of a SiC / SiC nuclear fuel cladding tube with the above-mentioned encapsulant, comprising: applying the encapsulant to the contact surface of the SiC / SiC cladding tube and the SiC end plug, drying and curing, heat treating in a high-temperature inert atmosphere, and finally cooling with the furnace to complete the encapsulation of the composite port of the SiC / SiC nuclear fuel cladding tube.

[0015] Preferably, the curing temperature is 70-140°C, and the time is 1-5 hours; the inert atmosphere is argon or helium; the heat treatment temperature is 1100-1400°C, the holding time is 1-5 hours, and the heating rate is 5-10°C / min.

[0016] In the present invention, a high thermal conductivity SiC phase and one-dimensional SiC whiskers with excellent mechanical properties are introduced into a traditional glass-ceramic encapsulant, and the formula ratio of the encapsulant is controlled to form a glass-ceramic connection layer reinforced with SiC whiskers and SiC particles, thereby effectively improving the mechanical and thermal properties of the cladding tube end plug connection and the structural stability in the LOCA state.

[0017] Beneficial effects:

[0018] The encapsulant for composite port encapsulation of accident-resistant SiC / SiC nuclear fuel cladding tubes of the present invention has the following advantages:

[0019] (1) The overall thermal neutron absorption cross section is small and has no adverse effect on the fission reaction.

[0020] (2) One-dimensional SiC whiskers act as a reinforcement phase, which significantly improves the mechanical properties of the bonding layer SiC / microcrystalline glass.

[0021] (3) The introduction of highly thermally conductive and diffusely distributed SiC phase improves the thermal properties of the traditional oxide glass-ceramic connection layer, thereby reducing the thermal stress at the cladding tube port connection under a loss of coolant accident, ultimately improving the safety margin in the pressurized water reactor design. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a process flow chart of the present invention; Figure 2 This is a scanning electron microscope image of the connection between the SiC end plug and the SiC / SiC cladding tube. DETAILED DESCRIPTION

[0023] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0024] The following is an exemplary description of a method for preparing a packaging agent for accident-resistant SiC / SiC nuclear fuel cladding tube composite port packaging provided by the present invention.

[0025] High-purity MgO, Al2O3, SiO2, and ZrO2 powders are mixed in a certain molar ratio, placed in a corundum crucible, heated, and stirred until melted and clarified, then quenched with water into glass powder and ground.

[0026] In an optional embodiment, the particle size of the high-purity MgO, Al2O3, SiO2, and ZrO2 powders is 0.5 to 10 μm, the purity is >99%, and the molar ratio is (15 to 40): (10 to 25): (35 to 50): (5 to 10); the purpose of selecting the glass powder is to regulate the softening point of the high-temperature melt to avoid excessive high-temperature liquid phase affecting the service performance of the connecting layer.

[0027] The heating temperature is 1500-1700°C for 30-120 minutes; the stirring rate is 30-60 rpm for 60-180 minutes; and the median diameter of the powder after grinding is 0.5-10 μm.

[0028] The obtained glass powder, SiC powder, SiC whisker, binder and solvent are mixed to obtain a paste-like composite port encapsulant.

[0029] In an optional embodiment, the particle size distribution of the SiC powder is 20μm:5μm:0.5μm=5:3:2, and the purity is >99%; the SiC powder introduced in the present invention does not react with the glass powder at high temperature and can be used as an inert filler to improve the mechanical properties and thermal conductivity of the connecting layer.

[0030] The SiC whisker has an aspect ratio of (20-50):1, a diameter of 0.2-0.5 μm, and a purity of >99%. The SiC whisker introduced by the invention does not react with glass powder at high temperatures and can be used as an inert reinforcement phase to improve the mechanical properties and thermal conductivity of the connection layer.

[0031] The binder is a compound of phenolic resin and silicone resin, and the mass ratio thereof is (1-3):1, for example, 2:1; the binder can impart certain mechanical properties to the connecting layer at room temperature, and form carbon-rich and silicon-rich substances respectively after high-temperature treatment, thereby correcting the stoichiometric ratio of the connecting layer.

[0032] The solvent is at least one of xylene, acetone and cyclohexane, and the purity is greater than 99%.

[0033] The volume ratio of the glass powder, SiC powder, SiC whisker, binder and solvent is (20-35):(5-10):(5-10):(3-50):(45-60); the purpose of controlling the volume ratio of the encapsulant within the above range is to avoid the encapsulant viscosity being too low to be coated or the viscosity being too high to form agglomerates in the connecting layer.

[0034] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0035] Example 1

[0036] (1) High-purity MgO, Al2O3, SiO2, and ZrO2 powders were uniformly mixed in a molar ratio of 40:10:40:10, placed in a corundum crucible, heated to 1600°C, and kept warm for 30 min. The glass liquid was stirred at a rate of 60 rpm / min for 60 min when the glass liquid changed from a molten state to a clarified state to homogenize the glass liquid, and then quenched with water and ground to obtain glass powder with a median diameter of 5 μm.

[0037] (2) Glass powder, SiC powder, SiC whisker, binder and acetone are fully mixed in a volume ratio of 35:10:7:3:45 to obtain a paste encapsulant.

[0038] (3) The joints between the SiC / SiC fuel cladding tube and the SiC end plug were ground, polished, ultrasonically cleaned and dried, and the paste encapsulant was evenly applied to the joint surface between the fuel cladding tube and the end plug. The joints were placed in an oven at 100 °C for drying and curing for 3 h. Subsequently, the joints were placed in a heating furnace under an argon atmosphere and heated to 1400 °C at a heating rate of 10 °C / min and kept at this temperature for 3 h. Finally, the joints were cooled with the furnace.

[0039] After testing, the thickness of the connection layer formed by the composite port encapsulant for accident-resistant SiC / SiC nuclear fuel cladding tube after high-temperature heat treatment is 113μm, the thermal conductivity is 31.7W / (m·K), and the thermal expansion coefficient is 4.1×10 -6 The load of the end plug push-out test is 4412N, and the load retention rate of the sample after one hot (1200℃)-cold (25℃) cycle is 69.7%.

[0040] Figure 2 This is a scanning electron microscope image of the connection between the SiC end plug and the SiC / SiC cladding tube. It can be seen from the figure that the two are well combined without obvious structural defects.

[0041] Example 2

[0042] (1) High-purity MgO, Al2O3, SiO2, and ZrO2 powders were uniformly mixed in a molar ratio of 15:25:50:10, placed in a corundum crucible, heated to 1500°C, and kept warm for 60 min. The glass liquid was stirred at a rate of 40 rpm / min for 120 min when the glass liquid changed from a molten state to a clarified state to homogenize the glass liquid, and then quenched with water and ground to obtain glass powder with a median diameter of 10 μm.

[0043] (2) Glass powder, SiC powder, SiC whisker, binder and xylene are fully mixed in a volume ratio of 30:5:5:5:55 to obtain a paste encapsulant.

[0044] (3) The joints between the SiC / SiC fuel cladding tube and the SiC end plug were ground, polished, ultrasonically cleaned and dried, and the paste encapsulant was evenly applied to the joint surfaces between the fuel cladding tube and the end plug. The joints were placed in an oven at 70°C for drying and curing for 5 h. The joints were then placed in a heating furnace and heated to 1250°C at a heating rate of 8°C / min in a helium atmosphere and kept at this temperature for 5 h. The joints were then cooled in the furnace.

[0045] After testing, the thickness of the connection layer formed by the composite port encapsulant for accident-resistant SiC / SiC nuclear fuel cladding tube after high-temperature heat treatment is 154μm, the thermal conductivity is 19.2W / (m·K), and the thermal expansion coefficient is 4.7×10 -6The load of the end plug push-out test is 3335N, and the load retention rate of the sample after one hot (1200℃)-cold (25℃) cycle is 75.4%.

[0046] Example 3

[0047] (1) High-purity MgO, Al2O3, SiO2, and ZrO2 powders were uniformly mixed in a molar ratio of 40:15:40:5, placed in a corundum crucible, heated to 1700°C, and kept warm for 120 min. The glass liquid was stirred at a rate of 30 rpm / min for 180 min when the glass liquid changed from a molten state to a clarified state to homogenize the glass liquid, and then quenched with water and ground to obtain glass powder with a median diameter of 0.5 μm.

[0048] (2) Glass powder, SiC powder, SiC whisker, binder and cyclohexane are fully mixed in a volume ratio of 20:6:10:4:60 to obtain a paste encapsulant.

[0049] (3) The joints between the SiC / SiC fuel cladding tube and the SiC end plug were ground, polished, ultrasonically cleaned and dried, and the paste encapsulant was evenly applied to the joint surface between the fuel cladding tube and the end plug. The joints were placed in an oven at 140°C for drying and curing for 1 h. Subsequently, the joints were placed in a heating furnace under an argon atmosphere and heated to 1100°C at a heating rate of 5°C / min and kept at this temperature for 1 h. Finally, the joints were cooled with the furnace.

[0050] After testing, the thickness of the connection layer formed by the composite port encapsulant for accident-resistant SiC / SiC nuclear fuel cladding tube after high-temperature heat treatment is 181μm, the thermal conductivity is 22.9W / (m·K), and the thermal expansion coefficient is 3.9×10 -6 The load of the end plug push-out test is 4774N, and the load retention rate of the sample after one hot (1200℃)-cold (25℃) cycle is 66.9%.

Claims

1. An encapsulant for accident-resistant SiC / SiC nuclear fuel cladding tube composite port encapsulation, characterized in that: include: The components are glass powder, SiC powder, SiC whisker, binder and solvent, wherein the molar ratio of MgO, Al2O3, SiO2 and ZrO2 in the glass powder is (15-40): (10-25): (35-50): (5-10); the volume ratio of the glass powder, SiC powder, SiC whisker, binder and solvent is (20-35): (5-10): (5-10): (3-50): (45-60).

2. The encapsulant according to claim 1, characterized in that The particle size distribution of the SiC powder is 20 μm: 5 μm: 0.5 μm = 5: 3: 2, and the purity is greater than 99%.

3. The encapsulant according to claim 1 or 2, characterized in that: The SiC whisker has an aspect ratio of (20-50):1, a diameter of 0.2-0.5 μm, and a purity of more than 99%.

4. The encapsulant according to any one of claims 1 to 3, characterized in that The binder is a compound of phenolic resin and silicone resin, with a mass ratio of (1-3):1, preferably 2:

1.

5. The encapsulant according to any one of claims 1 to 4, characterized in that The solvent is at least one of xylene, acetone and cyclohexane, and the purity is greater than 99%.

6. A method for preparing the encapsulant according to any one of claims 1 to 5, characterized in that: include: (1) High-purity MgO, Al2O3, SiO2, and ZrO2 powders are mixed in a certain molar ratio, placed in a crucible, heated, and stirred until melted and clarified, and then quenched into glass powder and ground; (2) The obtained glass powder, SiC powder, SiC whisker, binder and solvent are mixed to obtain a paste-like composite port encapsulant.

7. The preparation method according to claim 6, characterized in that: In step (1), the particle size of the high-purity MgO, Al2O3, SiO2, and ZrO2 powders is 0.5 to 10 μm, and the purity is >99%.

8. The preparation method according to claim 7, characterized in that: In step (1), the heating temperature is 1500-1700° C., and the time is 30-120 min; the stirring rate is 30-60 rpm / min, and the time is 60-180 min; and the median diameter of the powder after grinding is 0.5-10 μm.

9. A method for encapsulating a SiC / SiC nuclear fuel cladding tube composite port using the encapsulant according to any one of claims 1 to 5, characterized in that: include: The encapsulant is applied to the contact surface of the SiC / SiC cladding tube and the SiC end plug, dried and cured, heat treated in a high-temperature inert atmosphere, and finally cooled with the furnace to complete the encapsulation of the SiC / SiC nuclear fuel cladding tube composite port.

10. The method according to claim 9, characterized in that The curing temperature is 70-140° C., and the time is 1-5 hours; the inert atmosphere is argon or helium; the heat treatment temperature is 1100-1400° C., the heat preservation time is 1-5 hours, and the heating rate is 5-10° C. / min.

Citation Information

Patent Citations

  • SiC f / SiC core-clad tube port CaO-MgO-Al2O3-SiO2 glass encapsulation method

    CN109336634B

  • Method for encapsulating CaO-Y2O3-Al2O3-SiO2 glass at port of SiCf / SiC core cladding tube

    CN110903102A

  • Method for connecting SiC ceramic material by using calcium oxide / aluminum oxide / silicon dioxide / lithium oxide glass solder

    CN112851389A